2010
DOI: 10.1021/jo100111t
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Direct C−H Arylation Approach to Fused Purines. Synthesis of Purino[8,9-f]phenanthridines and 5,6-Dihydropurino[8,9-a]isoquinolines§Dedicated to the memory of Keith Fagnou.

Abstract: Intramolecular C-H arylations were employed as a key step in the synthesis of hitherto unknown fused purine systems: 13-substituted purino[8,9-f]phenanthridines and 11-substituted 5,6-dihydropurino[8,9-a]isoquinolines. The purino[8,9-f]phenanthridines were prepared in moderate yields by double C-H arylations of 9-phenylpurines with 1,2-diiodobenzene or, more efficiently, by consecutive Suzuki coupling of 9-(2-bromophenyl)purines with 2-bromophenylboronic acid followed by intramolecular C-H arylation. 5,6-Dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…The previous studies concerning the heterocyclic compounds, reported by our group and others,3a,11b,13 proved that the 2‐position of imidazole or benzimidazole could be a good site to be activated (Scheme ). Hence, we designed a coupling reaction between the 2‐position of imidazole or benzimidazole and a benzene ring.…”
Section: Methodsmentioning
confidence: 81%
“…The previous studies concerning the heterocyclic compounds, reported by our group and others,3a,11b,13 proved that the 2‐position of imidazole or benzimidazole could be a good site to be activated (Scheme ). Hence, we designed a coupling reaction between the 2‐position of imidazole or benzimidazole and a benzene ring.…”
Section: Methodsmentioning
confidence: 81%
“…Hence we shifted our focus on optimising the reaction parameters with respect to solvent, base, ligand and Cu source. Evaluation of Cu sources revealed that the reaction could be performed using Cu(OAc) 2 (Table entry 1–8). Among the bases screened, Cs 2 CO 3 was found to be superior which resulted in better conversions to arylaed/hetero arylated products.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Pd-catalyzed intermolecular double direct C-H arylation of 6-methyl-9- N- phenylpurine 31 with 1,2-diiodobenzene gave 32 (R = CH 3 ) in modest yield (35%). Alternatively, the sequential Suzuki coupling of 9-(2-bromophenyl)adenine 33 (R = NH 2 ) with 2-bromophenylboronic acid 34 followed by intramolecular C8-H arylation also gave the desired product 32 (R = NH 2 ) in moderate to high yields which preserves the base-pairing and major groove facets of the intact adenine ring (Scheme 10) [38]. However, attempted intramolecular oxidative coupling of 8,9-diphenyladenine failed to give 32 .…”
Section: Direct Activation Of C8-h Bond In Purine and Purine Nuclementioning
confidence: 99%